Efisiensi Energi Listrik Pada Gedung Apartement Menteng Park Jakarta - Sadikin, Ali; SusandI, Dony (Universitas Majalengka, 2025)
This research discusses the implementation of electrical energy efficiency at Menteng Park Apartment in Jakarta. As the need for electrical energy in the building sector increases, energy efficiency measures become crucial to reduce electricity consumption, operational costs, and negative environmental impacts. The research methods used include literature review, field study, 12-month energy consumption recording, calculation of energy consumption intensity (IKE), and forecasting using the time series method with SPSS software. The results show that Menteng Park Apartment's energy consumption exceeds the national efficiency standard, with an average usage of more than 950,000 kWh per month. Simulations of energy efficiency implementation, such as replacing conventional lamps with LEDs and optimizing the cooling system, show significant energy saving potential. The recommendations of this research are the implementation of energy-saving technology, integrated energy management, and sustainable energy conservation policies for apartment buildings.